Strength Training and the Risk of Type 2 Diabetes and Cardiovascular Disease - Shiroma, Eric J; Cook, Nancy R; Manson, Joann E; Moorthy, M V; Buring, Julie E; Rimm, Eric B; Lee, I-Min (Medicine and science in sports and exercise, 2017)
This study aimed to examine the association of strength training with incident type 2 diabetes and cardiovascular disease risk. We followed 35,754 healthy women (mean age = 62.6 yr, range = 47.0-97.8) from the Women's Health Study, who responded to a health questionnaire that included physical activity questions in 2000, assessing health outcomes through annual health questionnaire through 2014 (mean ± SD follow-up = 10.7 ± 3.7 yr). Incident type 2 diabetes (N cases = 2120) and cardiovascular disease (N cases = 1742) were confirmed on medical record review. Cases of cardiovascular disease were defined as confirmed cases of myocardial infarction, stroke, coronary artery bypass graft, angioplasty, or cardiovascular disease death. Compared with women who reported no strength training, women engaging in any strength training experienced a reduced rate of type 2 diabetes of 30% (hazard ratio = 0.70, 95% confidence interval = 0.61-0.80) when controlling for time spent in other activities and other confounders. A risk reduction of 17% was observed for cardiovascular disease among women engaging in strength training (hazard ratio = 0.83, 95% confidence interval = 0.72, 0.96). Participation in both strength training and aerobic activity was associated with additional risk reductions for both type 2 diabetes and cardiovascular disease compared with participation in aerobic activity only. These data support the inclusion of muscle-strengthening exercises in physical activity regimens for reduced risk of type 2 diabetes and cardiovascular disease, independent of aerobic exercise. Further research is needed to determine the optimum dose and intensity of muscle-strengthening exercises.